The Bibliometric Analysis of 3D Printer Research Development and Opportunities in Indonesia - Hasan Mastrisiswadi; Muhammad Kusumawan Herliansyah; Wangi Pandan Sari; Alva Edy Tontowi; Herianto (International Journal of Technology)
Indonesia is a large country in the ASEAN region with great potential to apply 3D printing technology. However, due to the archipelagic nature of the territory, the distribution process between islands is time consuming and expensive. The problems were promoted by the government to move the National Capital to other islands to improve efficiency and affordability of distribution channels. With respect to this analysis, 3D printers is a solution to the logistical challenges because it presented an opportunity for technology development in the 4.0 era. The finished products have numerous advantages such as low cost, fast process, creation of complex shapes with simple processes, and enabled the use of various materials. Therefore, this research aimed to determine how the opportunities associated with the use of 3D printers will be determined in the future. The bibliometric analysis method was used to quantitatively overview the research. The results showed that the growth of 3D printers in Indonesia increased annually by 14.6% in various fields of science. Additionally, it explored Indonesia global position, frequently targeted publications, institutions with the highest contribution, collaborating countries, prevalent topics, and future prospects.